“Tem bastante ponte, viaduto e prédios altos pra curar a doença deles”: um estudo dos discursos de internautas sobre os suicídios de pessoas não heterossexuais em uma rede social - Barbosa, Bruno Rafael Silva Nogueira (2020)
Suicide is a big problem of public health today. This phenomenon has been responsible for the death of more than 800,000 people worldwide each year (OPAS / OMS, 2016). However, little is said about this topic, especially because of its taboo social status. Because it is a multifactorial phenomenon, it receives interference from various factors, from the individual to the social. Vulnerability to this phenomenon is not linear and consistent, there are groups that are indicated as most vulnerable to this phenomenon among them are Lesbian, Gay, Bisexual, Transsexual, Transvestite, Transgender, Intersex - LGBTI +. The disparity between non-heterosexual and heterosexual persons with regard to propensity for suicidal ideations and attempts is well documented in the scientific literature. However, many people consider this theme as "less important", as a way of getting attention or as a search for "more rights than others". Thus, the aim of this study was to understand the discourses of Internet users about stories about suicide and nonheterosexual people shared by two journalistic pages in a social network. This is a digital ethnographic research using the technique of content analysis by thematic categorization. Four categories were found: 1) Gender Binarism, 2) Religious Bias, 3) Incentive / trivialization of suicide and 4) Victimism. The results point to the lack of knowledge of Internet users about suicidal behaviors, the stigmatization of subjects attempting suicide and the presence of religious and biologizing discourses to support prejudice against LGBTI + people. Thus, it was demonstrated the need to put into practice human rights guaranteed in the normative texts based on the elaboration of public policies and coordinated actions between the different areas.